Growth, yield and root qualities of two sweet potato (Ipomoea Batatas L.) Varieties as influenced by organic and inorganic fertilizer application - Nyarko, Albert (2016)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the award of Master of Philosophy In Agronomy (Crop Physiology) Degree, 2015